As práticas da aprendizagem colaborativa e dos multiletramentos desenvolvidas no uso do whatsapp por alunos dos 3° anos do ensino médio: um estudo em uma escola de ensino profissionalizante do município de Caucaia-CE - Lima, Maria Gezilane Gomes de (2022)
The present work discusses the practices of collaborative learning and multiliteracies developed in the use of WhatsApp by students of the 3rd year of high school, enrolled in a Vocational Education School in the city of Caucaia (CE). For this purpose, a ethnografy and qualitative case study was established as a methodology, based on a bibliographic research on the subject. As a hypothesis, it determined to answer the following question: How is the presence of collaborative learning and its connection with multiliteracies established in a virtual environment for sharing knowledge, created and managed by young high school students. Its general objective was to investigate the multiliteracies and sociability practices of young people autonomously in a high school educational context, during the preparation for the National High School Exam - ENEM, but specifically, in the preparation for the writing test. It was concluded that through the use of the messaging application by the observed students, a fact confirmed by the interviews carried out, a collaborative learning attached to multiliteracies was established, thanks to the expansion of research, vision and students' interpretation of the means in which could seek information to improve their writing focused on writing.